Investigations on Residual Stress Generation in Extruded Steel Components - Jobst, Andreas; Kiener, Christoph; Merklein, Marion (9th Congress of the German Academic Association for Production Technology (WGP), 2019)
During the forming of components, inhomogeneous stress conditions lead to residual stresses, which influence the operating behaviour of the manufactured part. Compressive residual stresses generally have a positive effect, while tensile residual stresses reduce the fatigue strength and facilitate crack initiation. Full forward extrusion has been established as an industrial manufacturing technique, where cylindrical billets are formed in the die and ejected in opposite direction. In order to influence the residual stresses state, it is essential to know about its formation. A basic understanding is created by separate investigation of the forming and the ejection step. In the context of this paper, singlephase ferritic stainless steel X6Cr17 and ferritic-austenitic duplex steel X2CrNi- MoN22-5-3 are used. The quantification of the residual stresses states is carried out by X-ray diffractometry, for which a measurement method for duplex steel is validated. The influence of forming and ejection is determined separately by manufacturing components with and without an ejection operation.<br
Keywords: Residual Stress; Forward Extrusion; Stainless Steel